Risk of dysphonia and voice quality in performing arts students - Ferrari, Eloisa Pinheiro (2023)
Purpose: To analyse the relationship between the risk of dysphonia and vocal quality in undergraduate performing arts students. Methods: Observational cross-sectional study with 38 undergraduate students in Performing Arts. We applied screening protocols for general and specific risk of dysphonia for actors and made recordings of sustained emission of the vowel /a/, spontaneous speech and reading a text, used for perceptual analysis performed by three evaluators using the GRBASI scale. After intra and inter-rater reliability tests it was obtained final classification of the general degree of vocal deviation parameter for each participant. Comparisons were made considering groups that had or did not have other profession/activity with the use of voice, and the groups were formed from the general grade. Results: Most students were at high risk for dysphonia. All had vocal alteration, with a predominance of mild degree. Students who had another profession/activity with voice use scored higher in the specific protocol for actors, and in the sum of this protocol with the general screening protocol. There was no relationship between the degree of vocal alteration and the risk of dysphonia. Students who did not yet work professionally had more moderate or severe vocal alterations, and those who did work professionally had a higher frequency of mild vocal alterations. Conclusion: Most students were at high risk for dysphonia. All had vocal alteration, with a predominance of mild alteration. There was no relationship between the risk of dysphonia and the degree of vocal alteration.